THE USE OF GAMES IN MATHEMATICS CLASSES FOR YOUTH AND ADULT EDUCATION - Eleide Corrêa de Souza, Clea; Pereira, Kariston (Journal of Interdisciplinary Debates, 2026)
This article examines playful activity as a methodological approach for teaching Mathematics in Youth and Adult Education (EJA), highlighting the role of games as mediators between everyday knowledge and formal school content. It begins from the understanding that Mathematics teaching—historically framed as an exact science and often distant from students’ lived realities—can acquire new meanings when games are incorporated as pedagogical strategies. The central objective is to discuss how the use of games, particularly dominoes, can enhance learning, logical reasoning, and student agency, fostering a more meaningful relationship with mathematical knowledge. Methodologically, this is a qualitative and descriptive study grounded in a literature review following the guidelines of Lakatos and Marconi (2017), and supported by authors who debate playfulness, Mathematics pedagogy, and the specificities of EJA. The results indicate that integrating games into Mathematics classes promotes engagement, socialization, and content comprehension, while also encouraging critical thinking and student self-confidence. The study concludes that games extend beyond a simple methodological resource; they constitute an emancipatory strategy capable of transforming learning into an interactive and meaningful experience